Dona-arbre de Fina Miralles - Viladomiu Canela, Àngels (2019)
The article analyzes the meaning of the binomial Woman-Tree through Fina Miralles’ work, pioneering artist of Catalan Conceptual Art. It also examines the connection various women artists who explore this theme within their work. They all share the use of the Woman-Tree image as a clear reference to female fertility and the meaning of the life cycle. Finally, it raises to what extent how the proposed work operate as an ecological report within the framework of ecofeminist thought